Robotic exoskeleton for rehabilitation and motion assist - Rahman, Md. Mozasser; Rahman, Mohammad Habibur; Kiguchi, Kazuo; Sasaki, Makoto (2006)
For elderly and or physically disabled people who have lost their body functioning of motions due to geriatric disorders, and/or disease processes including trauma, sports injuries, spinal cord injuries, occupational injuries, and strokes, we have been developing a 3DOF mobile robotic exoskeleton for rehabilitation and for assisting motion of elbow and shoulder, since human shoulder and elbow motions are involved in a lot of activities of everyday life. The robotic exoskeleton is mainly activated and is controlled by the skin surface electromyogram (EMG) signals,since EMG signals of muscles directly reflect how the user intends to move. This paper focused on the mechanism of mobile robotic exoskeleton and proposed passive and active assist mode of rehabilitation scheme in addition to assist daily upper-limb motion by the aid of robotic exoskeleton. The proportional derivative (PD) control has been applied to the controller for the passive mode of rehabilitation whereas neuro-fuzzy based biological controller is responsible for active assist mode of rehabilitation as well as to assist daily upper limb motion.